Visual Pollution and its Impact on the Aesthetics: The Town of Eizariya as a Model (Journal of Planner and Development, 2020)
This study seeks to shed light on the aspects of visual pollution and its impact on the aesthetics of the town of Al-Eizariya known to suffer from the phenomenon. In order to identify the real causes of the problem which develops in various forms and patterns, threatening not only the aesthetic appearance of the towns, but also causes the emergence of new problems and phenomena that will have negative repercussions on the population. The researcher uses the analytical descriptive method to analyze the phenomenon of visual pollution in terms of reality, development, manifestations and spread and uses photos which document the visual pollution and its impact on the aesthetics of the known. The study concluded the existence of a strong relationship between the level of cultural awareness of the population and the spread of visual pollution in the study area. The low awareness has caused many manifestations, also, there is a relationship between the role of the municipality and the spread of the phenomenon. The location of the study area is near the city of Jerusalem link between the north and the south of the West Bank played a role in a leading the emergence of visual pollution. Political factors contributed to the spread of many aspects of pollution. The study recommended the importance of increasing cultural awareness about the causes and dangers of visual pollution and ways to reduce it at the official and non-official levels. It is also necessary to organize publicity and advertising by setting technical, environmental and aesthetic standards and the activation of the public role to encounter this phenomenon.